Gestational weight gain in women with pre-pregnancy overweight or obesity and anthropometry of infants at birth - Mogensen, Christina Sonne; Zingenberg, Helle; Svare, Jens; Astrup, Arne; Magkos, Faidon; Geiker, Nina Rica Wium (Frontiers in Pediatrics, 2023)
Objective To examine the association of gestational weight gain (GWG) among women with pre-pregnancy overweight or obesity with infant weight and BMI z-score at birth. Methods This study is a secondary analysis of a randomized controlled trial including data from 208 infants at birth born by mothers with pre-pregnancy BMI between 28 and 45 kg/m2 who completed the APPROACH study (randomized to a high-protein low-glycemic index diet or a moderate-protein moderate-glycemic index diet). This analysis pooled the two diet treatment groups together and data were analyzed using a linear mixed model. Results Limiting GWG by 1 kg was associated with lower birthweight (−16 g, P = 0.003), BMI z-score (−0.03SD, P = 0.019), weight z-score (−0.03SD, P = 0.004), and infant abdominal circumference (−0.06 cm, P = 0.039). Infants born by mothers whose GWG was ≤9 kg weighed less (122 g, 95% CI: 6–249, P = 0.040), had similar BMI z-score (0.2SD, 95% CI: −0.06 to 0.55, P = 0.120), and lower incidence of emergency cesarean deliveries (11.5% vs. 23.1%, P = 0.044) compared to infants born by mothers whose GWG was >9 kg. When women were classified into GWG quartiles, women in Q1 (GWG range: −7.0 to 3.2 kg) gave birth to smaller infants (3,420 g, P = 0.015) with lower BMI z-score (−0.5SD, P = 0.041) than women in Q2 (3.3–7.1 kg), Q3 (7.2–10.9 kg) and Q4 (11.1–30.2 kg). Conclusions Limiting GWG among women with pre-pregnancy overweight or obesity was associated with lower infant weight, BMI z-score, weight z-score, and abdominal circumference at birth. Moreover, GWG below the Institute of Medicine guideline of a maximum of 9 kg was associated with lower birthweight and fewer emergency cesarean deliveries.